2015
DOI: 10.1371/journal.pone.0129964
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Tumorigenic Phosphorylation of p120 Catenin in Renal and Breast Cancer

Abstract: Altered protein expression and phosphorylation are common events during malignant transformation. These perturbations have been widely explored in the context of E-cadherin cell-cell adhesion complexes, which are central in the maintenance of the normal epithelial phenotype. A major component of these complexes is p120 catenin (p120), which binds and stabilizes E-cadherin to promote its adhesive and tumor suppressing function. However, p120 is also an essential mediator of pro-tumorigenic signals driven by onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…Furthermore, the presence of the basolateral E-cadherin complex was required for the induction of these pro-tumorigenic signals, via SRC activation and p120 phosphorylation 152 . Consistent with these results, this and other studies have shown extensive and early loss of PLEKHA7 in breast and kidney tumors, whereas E-cadherin was still expressed to a large extend and p120 phosphorylation was also increased in tumors 152154 . Collectively, these findings provided an explanation for the conflicting reports regarding the role of E-cadherin in anti- vs. pro-tumorigenic signaling.…”
Section: Beyond Emt: Cadherin Complexes and The Rnai Machinerysupporting
confidence: 91%
“…Furthermore, the presence of the basolateral E-cadherin complex was required for the induction of these pro-tumorigenic signals, via SRC activation and p120 phosphorylation 152 . Consistent with these results, this and other studies have shown extensive and early loss of PLEKHA7 in breast and kidney tumors, whereas E-cadherin was still expressed to a large extend and p120 phosphorylation was also increased in tumors 152154 . Collectively, these findings provided an explanation for the conflicting reports regarding the role of E-cadherin in anti- vs. pro-tumorigenic signaling.…”
Section: Beyond Emt: Cadherin Complexes and The Rnai Machinerysupporting
confidence: 91%
“…Intriguingly, recent work on the whole genome level has indicated that Kaiso is largely associated with transcriptional activation as opposed to repression (Blattler et al, 2013); if this proves the case, it will be important to establish if p120 additionally has a role in this context. As part of earlier mentioned work, p120 phosphorylation at Y228 is predictive of glioblastoma multiforme (GBM) invasiveness (Huveldt et al, 2013), and is also elevated in invasive renal and breast tumors (Kourtidis et al, 2015). Further, T916 phosphorylation is high in these tumors; and while the functional role of phospho-T916 was not resolved, it was found to obstruct the epitope of the widely employed pp120 monoclonal antibody.…”
Section: P120-catenin Isoforms and Phosphorylation In Cancermentioning
confidence: 95%
“…Recent work has furthermore identified DIPA as a binding partner specific for p120-isoform 1 (Klompstra et al, 2015; Markham et al, 2012; Markham et al, 2014), and an amino-terminal region preceding p120’s coiled-coil domain is an important binding site for kinesin (Figure 1). Given that other proteins associate with p120’s amino-terminal region, such as NLBP, PLEKHA7 and RPTPµ, future tests must assess the isoform specificity of these interactions (Chen et al, 2003; Kim et al, 2013; Kourtidis et al, 2015; Kurita et al, 2013; Markham et al, 2014; Meng et al, 2008; Pulimeno et al, 2010). …”
Section: Phosphorylation Of P120-cateninmentioning
confidence: 99%
See 2 more Smart Citations